If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 8y = 11y + -17 Reorder the terms: 4 + 8y = -17 + 11y Solving 4 + 8y = -17 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. 4 + 8y + -11y = -17 + 11y + -11y Combine like terms: 8y + -11y = -3y 4 + -3y = -17 + 11y + -11y Combine like terms: 11y + -11y = 0 4 + -3y = -17 + 0 4 + -3y = -17 Add '-4' to each side of the equation. 4 + -4 + -3y = -17 + -4 Combine like terms: 4 + -4 = 0 0 + -3y = -17 + -4 -3y = -17 + -4 Combine like terms: -17 + -4 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| 24-6x+2x=12 | | 5j= | | 12*1x-17=20 | | x+3(x-1)=13 | | 3x-5y=-4 | | 26=5(w+4)-8w | | 2+4b=2+2b | | 4x=15+1X | | 5x^2-41x+8= | | 5x-4=180 | | 13-1x*14=9 | | 5(w)=84 | | 50-23d-d^2=0 | | x-9+3x=-14 | | 1=2u+7 | | -5(2x+-10)=-35x+50+25x | | 1=7+2 | | 7.50+1m=2.50m | | y^3-4y^2+3y=o | | 14x-(-3)=5 | | 5(2n+3)-5=-70 | | 17x*6x-4*3=10 | | 0=x^2-10x+24 | | 5(40x-260)-25(80-20x)=226 | | 13-5x+7x-19=37 | | -8n+2n=-8-7n | | 25+.10x=35+.5x | | -1(3x+-13)=37 | | 0=5(7-x)+12 | | k-8=4 | | 5x+8=7c-0 | | 1.5-(32.8)= |